Assessment of immunization status among under five children in a census town of South India - Basti, Bharatesh Devendra; Rajegowda, Ravi Marinayakanahalli; Varaprasad, Devi; Pitchandi, Janakiraman (International Journal Of Community Medicine And Public Health, 2019)
Background: Deaths among children of less than five years are preventable, mostly by vaccination. In India, the coverage still remains low, as low as 44% children between 12 to 23 months age are fully immunized. This study was intended to assess the immunization status of the children between the age group of 12-60 months, and study the possible socio demographic factors influencing it. Methods: This cross-sectional study was conducted in 16 wards of a census town, selected by Multi-stage simple random sampling, for a period of 4 months among 400 children. Data was collected from the mothers of these children, using structured questionnaire. Results: Immunization status among these children showed that 32.5% were fully immunized, 52.0% were immunisation update, 14% were partially immunized, and 0.5% was not immunized. Immunization status was highest for BCG and OPV-0 (99%) and least for Measles 2nd dose and DPT booster (52%). Inadequate knowledge about immunization was the most common reason for partial and un-immunization. Multivariate Logistic regression analysis showed that, factors like religion (Hindus had 2.843 odds of being partially immunised than other religions), availability of Immunization card (Those without Immunisation card had 2.025 odds of being partially immunised than those with immunisation card) and place of immunization (Those immunised at private facilities had 1.441 odds of being partially immunised than those at government facilities), were found to be significantly associated with the immunization status of the child. Conclusions: Government facilities remain the main pillars of immunisation. Coordination with Anganwadi centres is the key. Tracking of the child for subsequent doses of immunisation remains a challenge.